2006
DOI: 10.1090/s0002-9939-06-08664-3
|View full text |Cite
|
Sign up to set email alerts
|

On the finiteness properties of extension and torsion functors of local cohomology modules

Abstract: Abstract. Let R be a commutative Noetherian ring with non-zero identity, a and b ideals of R with a ⊆ b,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The part i follows from Theorem 2.10 and the fact that the Bass numbers of finitely generated modules are finite. Also, ii follows from Theorem 2.10 and [11,Corollary 3.5].…”
Section: M/s M/t / S/t = N/kmentioning
confidence: 97%
“…The part i follows from Theorem 2.10 and the fact that the Bass numbers of finitely generated modules are finite. Also, ii follows from Theorem 2.10 and [11,Corollary 3.5].…”
Section: M/s M/t / S/t = N/kmentioning
confidence: 97%
“…Huneke and Sharp [9] (in the case of positive characteristic) and Lyubeznik [17] (in characteristic zero) have shown that if R is regular local ring containing a field, then H n a ðRÞ has only finitely many associated primes for all n A N. Afterward, Lyubeznik [18] has prove this result also holds for any unramified regular local ring of mixed characteristic. We refer the reader to the papers of [21], [14], [22], [28] and [12]. There are several papers devoted to the extension of the above results.…”
Section: Introductionmentioning
confidence: 96%
“…This result inspired us to study Tor R i (R/a, H j a (X)) in general for an arbitrary R-module X. Note that there are some attempts to study Tor R 0 (R/a, H j a (X)) in [2] and Tor R i (R/a, H j a (M )) in [10].…”
Section: Introductionmentioning
confidence: 98%